2022
DOI: 10.1186/s13075-022-02848-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wnt/β-catenin signaling contributes to autophagy inhibition resulting from a dietary magnesium deficiency in injury-induced osteoarthritis

Abstract: Background Dietary magnesium deficiency, which is common in modern diet, has been associated with osteoarthritis (OA) susceptibility. Despite this clinical association, no study has addressed if dietary magnesium deficiency accelerates OA development, especially at molecular level. This study aimed to explore aggravating effects of dietary magnesium deficiency on cartilage damage in an injury-induced murine OA model and to determine the underlying mechanism. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…13 Recent investigation into OA shows articular chondrocyte homeostasis could be disrupted by overweight, aging as well as genetic alterations in tumor growth factor (TGF)-β/Smad, Wnt/β-catenin, and Ihh signaling pathways. [14][15][16][17] The upregulation of catabolic enzymes like matrix metalloproteinases (MMP)-13 and ADAMTS5 in most mouse models of OA suggest that these enzymes may serve as the potential therapeutic targets in the intervention of the progression of the OA. 18 Recently, with the development of high-throughput sequencing technology, more and more studies have attempted to find the possible and potential mechanism of the pathogenesis and progression of OA by performing multi-omics sequencing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Recent investigation into OA shows articular chondrocyte homeostasis could be disrupted by overweight, aging as well as genetic alterations in tumor growth factor (TGF)-β/Smad, Wnt/β-catenin, and Ihh signaling pathways. [14][15][16][17] The upregulation of catabolic enzymes like matrix metalloproteinases (MMP)-13 and ADAMTS5 in most mouse models of OA suggest that these enzymes may serve as the potential therapeutic targets in the intervention of the progression of the OA. 18 Recently, with the development of high-throughput sequencing technology, more and more studies have attempted to find the possible and potential mechanism of the pathogenesis and progression of OA by performing multi-omics sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recent investigation into OA shows articular chondrocyte homeostasis could be disrupted by overweight, aging as well as genetic alterations in tumor growth factor (TGF)-β/Smad, Wnt/β-catenin, and Ihh signaling pathways. 14 -17 The upregulation of catabolic enzymes like matrix metalloproteinases (MMP)-13 and ADAMTS5 in most mouse models of OA suggest that these enzymes may serve as the potential therapeutic targets in the intervention of the progression of the OA. 18…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is an element that is mainly stored in the skeletal system and plays a crucial role in maintaining bone and cartilage health (13)(14)(15)(16). Previous studies have revealed the link between magnesium ion (Mg 2+ ) deficiency and the progression of OA (17,18). Notably, oral and intra-articular Mg 2+ supplementation has shown beneficial effects in OA treatment (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is greatly influenced by magnesium, but the effect is quite complex. Studies have reported that dietary magnesium deficiency reduces the number of autolysosomes and autophagosomes [ 34 ]. Magnesium incorporated in biomaterials triggers autophagy to mediate apoptosis in osteosarcoma cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%